VARIASI EKSTRAK DAUN JAMBU BIJI MERAH (Psidium guajava L.) PADA LULUR BODY SCRUB - Densi Selpia Sopianti; Laila Munawara (Oceana Biomedicina Journal, 2022)
Red guava is a plant that is easily found in the tropics, especially in Indonesia. In addition to the fruit that is used, many people use red guava leaves as a natural cosmetic. One of the contents of red guava leaves is 17.4% flavonoids, which is one of the functions of these flavonoids as an antioxidant that can counteract free radicals which these free radicals can damage body cells. The purpose of this study was to obtain the best formula from variations of red guava leaf extract (Psidium guajava L.) in body scrub preparations. The extract was made by maceration method using 96% ethanol solvent, the variation of extract used was F0=0%, F1=4%, F2=6%, F3=8%. Body scrub scrub from Psidium guajava extract was evaluated including organoleptic test, homogeneity test, pH test, stability test, viscosity test, adhesion test, spreadability test, and cream type test. The results of the study showed the variation consentration is that red guava leaf extract (Psidium guajava L) can be formulated as a body scrub preparation. And the evaluation that has been done, then the concentration variations of red guava leaf extract affect the physical properties of the resulting lulur, especially on organoleptic and viscosity. The higher the concentration of red guava leaf extract, the darker the color and the thicker it is. Does not affect the spreadability, pH and adhesion